2010
DOI: 10.1667/rr1789.1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Diseases in the Cohort of Workers First Employed at Mayak PA in 1948–1958

Abstract: Incidence of and mortality from cardiovascular diseases have been studied in a cohort of 12,210 workers first employed at one of the main plants of the Mayak nuclear facility during 1948-1958 and followed up to 31 December 2000. Information on external gamma-ray doses is available for virtually all of these workers (99.9%); the mean total gamma-ray dose (+/-SD) was 0.91 +/- 0.95 Gy (99% percentile 3.9 Gy) for men and 0.65 +/- 0.75 Gy (99% percentile 2.99 Gy) for women. In contrast, plutonium body burden was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 30 publications
4
90
0
1
Order By: Relevance
“…Many studies lack this information on lifestyle factors. Of the studies considered in Table 7 only those of the Japanese atomic-bomb survivors [7,48], Mayak workers [49,50], and Canadian fluoroscopy patients [15] had such information. Some lifestyle factors were included in the Nordic breast cancer case-control study [4], and specific medical factors (surgery, thoracoplasty, pneumolobectomy), alcohol consumption, and cigarette smoking were included in the cohort considered here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies lack this information on lifestyle factors. Of the studies considered in Table 7 only those of the Japanese atomic-bomb survivors [7,48], Mayak workers [49,50], and Canadian fluoroscopy patients [15] had such information. Some lifestyle factors were included in the Nordic breast cancer case-control study [4], and specific medical factors (surgery, thoracoplasty, pneumolobectomy), alcohol consumption, and cigarette smoking were included in the cohort considered here.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of these findings is unclear, and they may best be interpreted as the effects of chance. In all other radiation-exposed groups with such information there is no evidence that lifestyle factors interacted with radiation risk [4,7,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…4 Nevertheless, in most women, the heart still receives doses of 1 to 5 Gy. [5][6][7][8][9][10][11] Several studies have suggested that exposures at this level can cause is che mic heart disease, [12][13][14] but the magnitude of the risk after any given dose to the heart is uncertain, as are the time to the development of any radiation-related disease and the influence of other cardiac risk factors. We therefore conducted a study relating the risk of is chemic heart disease after radiotherapy to each woman's radiation dose to the heart and to any cardiac risk factors she had at the time of radiotherapy.…”
mentioning
confidence: 99%
“…and digestive systems, was reported in [22], which can be seen as circumstantial evidence in favor of dose-related differences in medical surveillance and self-reporting, a phenomenon noticed also by other researchers in populations exposed to radiation [28], discussed in [29]. In the author's opinion, the dose-effect relationships with non-neoplastic diseases [30][31][32][33][34] call in question such relationships with cancer, reported e.g. in the studies [23,24,[35][36][37][38][39][40][41][42][43] including those cited in [2,25] in support of the DDREF lowering.…”
Section: Discussion Around Dose and Dose Rate Effectiveness Factor (Dmentioning
confidence: 73%